Graphene-reinforced microalloyed titanium matrix composite and method of making the same

CN117904492BActive Publication Date: 2026-10-16HARBIN INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410143341.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-01
Publication Date
2026-10-16
Estimated Expiration
2044-02-01

AI Technical Summary

Technical Problem

[0009]本发明的目的是提供一种石墨烯增强微合金化钛基复合材料及其制备方法,以解决在制备综合性能更优异的石墨烯/Ti基复合材料过程中,石墨烯极易与钛发生严重的界面反应,导致制备的石墨烯/Ti基复合材料与纯Ti相比,强度提高程度较小,同时伴随塑性降低的问题

Benefits of technology

[0022] (1) The graphene-reinforced microalloyed titanium-based composite material prepared by the present invention can significantly reduce the interfacial reaction between graphene and titanium through reasonable component ratio and ball milling and sintering settings, providing a new idea for the research of graphene-reinforced titanium-based composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117904492B_ABST
    Figure CN117904492B_ABST
Patent Text Reader

Abstract

The application discloses a graphene reinforced microalloyed titanium-based composite material and a preparation method thereof, and belongs to the technical field of graphene / titanium-based composite materials.The graphene reinforced microalloyed titanium-based composite material prepared by the application can significantly reduce the interface reaction between graphene and titanium through reasonable component proportioning and ball milling and sintering setting, and provides a new thought for the research of graphene reinforced titanium-based composite materials;the graphene reinforced microalloyed titanium-based composite material prepared by the application has a density of 4.62 g / cm 3 , a compactness of 99.25%, and a microhardness of 590 HV, and compared with pure Ti, the microhardness is increased by 293%-743%, and the yield strength is increased by more than 100% than that of pure titanium and graphene / Ti composite material without adding alloy elements;the preparation method is simple and easy to operate, has high preparation efficiency, saves energy, is environment-friendly in the preparation process, generates no toxic and harmful substances, and can be used for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of graphene / titanium-based composite materials technology, and in particular to a graphene-reinforced microalloyed titanium-based composite material and its preparation method. Background Technology

[0002] Titanium is a silvery-white transition metal and an important alloying element. It has the highest specific strength among metals, a melting point of 1668℃, a latent heat of fusion of 3.7-5.0 kcal / g atom, a boiling point of 3260±20℃, a latent heat of vaporization of 102.5-112.5 kcal / g atom, a critical temperature of 4350℃, and a critical pressure of 1130 atm.

[0003] The main characteristics of titanium are as follows: low density, 43% less than steel, and slightly higher than the renowned lightweight metal magnesium; high mechanical strength, with pure titanium having a tensile strength of up to 180 kg / mm². 2 It is similar to steel, twice as strong as aluminum, and five times as strong as magnesium. Although some steels have higher strength than titanium / titanium alloys, the specific strength (the ratio of tensile strength to density) of titanium / titanium alloys exceeds that of high-quality steel. It is resistant to high temperatures, with a melting point of 1942K, which is nearly 1000K higher than gold and nearly 500K higher than steel.

[0004] It is malleable and easy to process; high-purity titanium can have an elongation of 50-60% and a reduction of area of ​​70-80%, but its shrinkage strength (i.e., the force generated during shrinkage) is low. Its thermal and electrical conductivity is poor, similar to or slightly lower than that of stainless steel. It is superconducting; the superconducting critical temperature of pure titanium is 0.38-0.4K. It is a non-magnetic metal and is difficult to magnetize even in a strong magnetic field. Its tensile strength is close to its yield strength, and its yield ratio is high. Correspondingly, titanium materials have poor plastic deformation during forming. Due to the large ratio of titanium's yield limit to its elastic modulus, titanium has a high springback ability during forming. It has excellent corrosion resistance, so it is often used in the chemical industry.

[0005] The presence of other metallic or non-metallic components in titanium has a significant impact on its mechanical properties. In particular, interstitial impurities (oxygen, nitrogen, carbon) can greatly increase titanium's strength but significantly reduce its plasticity. By strictly controlling the types and contents of other components in titanium, titanium alloys with different mechanical properties and characteristics can be obtained, making them suitable for various fields. With the development of my country's industry towards high-precision and sophisticated fields, titanium and titanium alloys are playing an increasingly important role in the national economy, finding increasingly widespread applications in aerospace, defense, marine engineering, chemical industry, automotive industry, and petroleum industry.

[0006] Low-temperature titanium alloys, such as TA7 (Ti-5Al-2.5Sn), TC4 (Ti-6Al-4V), and Ti-2.5Zr-1.5Mo, exhibit increased strength with decreasing temperature, but with minimal change in plasticity. They maintain good ductility and toughness at temperatures ranging from -196 to 253℃, avoiding cold brittleness and making them ideal materials for cryogenic containers, storage tanks, airfoils, and other equipment.

[0007] Titanium alloys possess excellent heat resistance, low-temperature toughness, and fracture toughness, making them widely used in aircraft engine parts and rocket and missile structural components. They are also used as storage tanks for dyes and oxidizers, as well as high-pressure containers. Titanium alloys are already being used to manufacture automatic rifle base plates, mortar base plates, and recoilless rifle tubes. In the petroleum industry, they are mainly used for various containers, reactors, heat exchangers, distillation towers, pipes, pumps, and valves. Titanium-nickel shape memory alloys are widely used in instrumentation. In medicine, titanium / titanium alloys are also used to make artificial bones. Titanium carbide and titanium hydride are new types of hard alloy materials.

[0008] However, after decades of development, the performance of titanium alloys has gradually approached its limits. Further improving the overall performance of titanium alloys, especially in extreme environments with high temperatures and high strain rates, and realizing their wider application, remains a perpetual pursuit for researchers in this field. In recent years, graphene / Ti composites have exhibited superior strength, plasticity (toughness), and impact resistance, attracting widespread attention from researchers both domestically and internationally. However, due to the extremely high chemical reactivity of titanium, the problem of severe interfacial reactions between graphene and titanium remains a significant challenge in the design and preparation of graphene / Ti composites. Summary of the Invention

[0009] The purpose of this invention is to provide a graphene-reinforced microalloyed titanium-based composite material and its preparation method, in order to solve the problem that in the process of preparing graphene / Ti-based composite materials with better comprehensive performance, graphene is prone to severe interfacial reaction with titanium, resulting in a smaller increase in strength and a decrease in plasticity compared with pure Ti.

[0010] To achieve the above objectives, the present invention provides a graphene-reinforced microalloyed titanium-based composite material and its preparation method. The graphene-reinforced microalloyed titanium-based composite material is composed of the following components in mass fraction: Ta 0.70-0.90%, Mo 0.90-1.10%, Sn 1.10-1.30%, graphene 0.90-1.10%, and the remainder being Ti and other unavoidable impurity elements.

[0011] Preferably, it consists of the following components in mass fractions: Ta 0.75-0.85%, Mo 0.95-1.05%, Sn 1.15-1.25%, graphene 0.95-1.05%, with the remainder being Ti and other unavoidable impurity elements.

[0012] Preferably, it consists of the following components by mass fraction: Ta 0.85%, Mo 1.01%, Sn 1.19%, graphene 1.00%, with the remainder being Ti and other unavoidable impurity elements.

[0013] Preferably, it consists of the following components in mass fractions: Ta 0.70%, Mo 0.90%, Sn 1.10%, graphene 0.90%, with the remainder being Ti and other unavoidable impurity elements.

[0014] Preferably, it consists of the following components by mass fraction: Ta 0.90%, Mo 1.10%, Sn 1.30%, graphene 1.10%, with the remainder being Ti and other unavoidable impurity elements.

[0015] A method for preparing the graphene-reinforced microalloyed titanium-based composite material as described above includes the following steps:

[0016] S1. Ball milling: Add all raw materials and grinding balls into the ball mill jar, place the ball mill jar on the ball mill, set the main disc speed to 300 rpm / min, and the ball milling time to 20 h. Use the ball milling mode of 20 min ball milling and 10 min intermittent grinding. After the ball milling is completed, the composite powder is obtained.

[0017] S2. The obtained composite powder is subjected to plasma sintering. The sintering process parameters are set as follows: vacuum degree 5Pa, heating rate 40-60℃ / min, sintering temperature 1000℃, axial pressure 40MPa, holding time 20min, and cooling rate 50℃ / min.

[0018] Preferably, in step S1, the grinding jar is made of hardened chromium steel, and the grinding balls are made of ZrO2 material. The ratio of grinding balls with a diameter of 10mm to grinding balls with a diameter of 6mm is 3:4.

[0019] Preferably, in step S1, the grinding jar needs to be cleaned with a brush and dried with water before loading the grinding balls and components, and then cleaned and dried with anhydrous ethanol; the ball-to-material mass ratio is 2:1; before placing the grinding jar on the ball mill, it is vacuumed three times in a vacuum environment.

[0020] Application of a graphene-reinforced microalloyed titanium-based composite material as described above.

[0021] Therefore, the graphene-reinforced microalloyed titanium-based composite material and its preparation method provided by this invention have the following specific technical effects:

[0022] (1) The graphene-reinforced microalloyed titanium-based composite material prepared by the present invention can significantly reduce the interfacial reaction between graphene and titanium through reasonable component ratio and ball milling and sintering settings, providing a new idea for the research of graphene-reinforced titanium-based composite materials.

[0023] (2) The graphene-reinforced microalloyed titanium-based composite material prepared in this invention has a density of 4.62 g / cm³. 3 The density is 99.25%, the microhardness is 590HV, and the microhardness is increased by 293%-743% compared with pure Ti. The yield strength is more than 100% higher than that of pure titanium and graphene / Ti composites without alloying elements.

[0024] (3) The preparation method of graphene-reinforced microalloyed titanium-based composite material provided by the present invention is simple and easy to operate, has high preparation efficiency, saves energy, and is environmentally friendly in the preparation process, without generating any toxic or harmful substances, and can be used for industrial production.

[0025] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0026] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a secondary electron image (SEM) of the graphene-reinforced microalloyed titanium-based composite material prepared according to Example 1 of the present invention.

[0028] Figure 2 This is a SEM backscattered image of the graphene-reinforced microalloyed titanium-based composite material prepared according to Example 1 of the present invention. Detailed Implementation

[0029] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0030] To make the objectives, technical solutions, and advantages of this application clearer, more thorough, and more complete, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments. The following detailed descriptions are all illustrations of embodiments, intended to provide further detailed explanation of the present invention. Unless otherwise specified, all technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0031] The raw materials and instruments used in the examples were all obtained commercially.

[0032] Example 1

[0033] A graphene-reinforced microalloyed titanium-based composite material was prepared by the following method:

[0034] S1. Clean the grinding jar made of hardened chromium steel and the grinding balls made of ZrO2 with clean water and a brush, let them air dry, then clean them three times with 75% ethanol, and then blow them dry. Each grinding jar contains 30 large grinding balls with a diameter of 10 mm and 40 small grinding balls with a diameter of 6 mm.

[0035] Using an analytical balance, the following raw materials were weighed at a ball-to-powder ratio of 2:1: 95.95 g of pure Ti powder, 1.00 g of graphene, 0.85 g of Ta powder, 1.01 g of Mo powder, and 1.19 g of Sn powder. These were then sequentially poured into a ball mill jar. After three vacuum extractions under vacuum, the jar was placed on a ball mill. The main disc speed was set to 300 rpm / min, and the milling time was 20 hours. A 20-minute milling interval followed by a 10-minute interval was used for the mixed ball milling. The composite powder was obtained after the mixed ball milling was completed.

[0036] S2. The obtained composite powder is subjected to plasma sintering. The sintering process parameters are set as follows: vacuum degree 5 Pa, heating rate 50℃ / min, sintering temperature 1000℃, axial pressure 40 MPa, holding time 20 min, and cooling rate 50℃ / min. The graphene-reinforced microalloyed titanium-based composite material is obtained when the temperature is reduced to ambient temperature.

[0037] Example 2

[0038] A graphene-reinforced microalloyed titanium-based composite material was prepared using the same method as in Example 1, except that the raw materials were weighed using an analytical balance at a ball-to-material ratio of 2:1: 96.40 g of pure Ti powder, 0.90 g of graphene, 0.70 g of Ta powder, 0.90 g of Mo powder, and 1.10 g of Sn powder.

[0039] Example 3

[0040] A graphene-reinforced microalloyed titanium-based composite material was prepared using the same method as in Example 1, except that the raw materials were weighed using an analytical balance at a ball-to-material ratio of 2:1: 95.60 g of pure Ti powder, 1.10 g of graphene, 0.90 g of Ta powder, 1.10 g of Mo powder, and 1.30 g of Sn powder.

[0041] Example of effect 1

[0042] The microstructure of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 was observed using the following method:

[0043] A. The graphene-reinforced microalloyed titanium-based composite material obtained in Example 1 was wire-cut to obtain a sample block with a size of 5mm×5mm×5mm. The surface of the sample block was ground with 120#, 240# and 600# sandpaper in sequence until there were no obvious scratches on the surface. Then, it was polished carefully on a polishing machine. Water was continuously injected while the polishing machine was rotating until the surface of the sample block reached a scratch-free and bright state.

[0044] B. Immerse the sample in a etching solution consisting of 7 mL H₂O, 1 mL HF, and 2 mL HNO₃ for 3 seconds. Then, observe the etched graphene-reinforced microalloyed titanium-based composite material sample using a scanning electron microscope. The microstructure of the graphene-reinforced microalloyed titanium-based composite material is shown in the image below. Figure 1 and Figure 2 As shown, where Figure 1 This is a secondary electron image (SEM) of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1. Figure 2 This is a SEM backscattered image of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1.

[0045] Depend on Figure 1 and Figure 2 It can be seen that the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 has a matrix phase mainly consisting of α-Ti phase; the second phase generated in the graphene-reinforced microalloyed titanium-based composite material is dispersed on the matrix, and the particles of the second phase are fine and uniform.

[0046] Example of effect 2

[0047] The density and compactness of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 were tested using the following methods:

[0048] After the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 was cleaned with sandpaper, it was ultrasonically cleaned, and then the surface of the composite material was dried. The density of the graphene-reinforced microalloyed titanium-based composite material was measured by the water displacement method, and the measurement was repeated 3 times.

[0049] The actual density calculation formula is: Where ρ S The actual measured density of the sample (g / cm³) 3 ), m1 is the mass of the sample in air (g), m2 is the mass of the sample in deionized water (g), ρ h The density of deionized water (g / cm³) 3 ).

[0050] The theoretical density is calculated based on the mixing principle, and the formula is: ρ l=∑ρ i V i , where ρ L The theoretical density (g / cm³) of the sample. 3 ), ρ i The theoretical density of the i-th phase (g / cm³) 3 V i Let be the volume fraction (vol%) of the i-th phase.

[0051] The formula for calculating density is: η is the density (%) of the sample.

[0052] The results showed that the density of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 was 4.62 g / cm³. 3 The density is 99.25%.

[0053] Example of effect 3

[0054] The mechanical properties of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 were tested using the following methods:

[0055] The hardness of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 was tested using a hardness tester (HV1000IS Vickers microhardness tester) with a pressure value of 200g and a holding time of 6s.

[0056] The results show that the microhardness of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 is 590 HV, while the microhardness of industrial pure titanium is 70-150 HV. That is, the microhardness of the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 is 293%-743% higher than that of industrial pure titanium.

[0057] Compression tests were performed on the graphene-reinforced microalloyed titanium-based composite material prepared in Example 1 using an MTS810 electronic universal testing machine. The sample size was Φ4×6mm, and the test temperatures were room temperature, 300℃, and 600℃. The maximum load of the equipment was 100KN, and the compression rate was 1mm / min. The relevant test results for the unalloyed graphene / Ti composite material can be found in *The Preparation and Mechanical Properties of a Pure Titanium-Based Matrix Composite Reinforced with Graphene Nanoplatelets*, 2020, *Science of Advanced Materials*, Zaiyu Zhang et al. The test results are shown in Table 2.

[0058] Table 2

[0059]

[0060] The graphene-reinforced microalloyed titanium-based composite material has a microhardness of 590 HV, a yield strength of 1850 MPa, a compressive strength of 2248 MPa, and a fracture strain of 19%.

[0061] Therefore, the graphene-reinforced microalloyed titanium-based composite material prepared in this invention, through reasonable component ratios and ball milling and sintering settings, can significantly reduce the interfacial reaction between graphene and titanium, providing a new approach for the research of graphene-reinforced titanium-based composite materials; the prepared graphene-reinforced microalloyed titanium-based composite material has a density of 4.62 g / cm³. 3 The density is 99.25%, and the microhardness is 590 HV. Compared with pure Ti, the microhardness is increased by 293%-743%, and the yield strength is increased by more than 100% compared with pure titanium and graphene / Ti composites without alloying elements. The preparation method is simple and easy to operate, with high preparation efficiency and energy saving. Moreover, the preparation process is environmentally friendly, with no toxic or harmful substances generated, and can be used for industrial production.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A graphene-reinforced microalloyed titanium-based composite material, characterized in that, It consists of the following components by mass fraction: Ta 0.70-0.90%, Mo 0.90-1.10%, Sn 1.10-1.30%, graphene 0.90-1.10%, with the remainder being Ti and other unavoidable impurity elements; The preparation method of the graphene-reinforced microalloyed titanium-based composite material includes the following steps: S1. Ball milling: Add all raw materials and grinding balls into the ball mill jar, place the ball mill jar on the ball mill, set the main disc speed to 300 rpm / min, and the ball milling time to 20 h. Use the ball milling mode of 20 min ball milling and 10 min intermittent grinding. After the ball milling is completed, the composite powder is obtained. S2. The obtained composite powder is subjected to plasma sintering. The sintering process parameters are set as follows: vacuum degree 5Pa, heating rate 40-60℃ / min, sintering temperature 1000℃, axial pressure 40MPa, holding time 20min, cooling rate 50℃ / min. In step S1, the grinding jar is made of hardened chromium steel and the grinding balls are made of ZrO2 material. The ratio of grinding balls with a diameter of 10mm to grinding balls with a diameter of 6mm is 3:

4.

2. The graphene-reinforced microalloyed titanium-based composite material according to claim 1, characterized in that, It consists of the following components by mass fraction: Ta 0.75-0.85%, Mo 0.95-1.05%, Sn 1.15-1.25%, graphene 0.95-1.05%, with the remainder being Ti and other unavoidable impurity elements.

3. The graphene-reinforced microalloyed titanium-based composite material according to claim 1, characterized in that, It consists of the following components by mass fraction: Ta 0.85%, Mo 1.01%, Sn 1.19%, graphene 1.00%, with the remainder being Ti and other unavoidable impurity elements.

4. The graphene-reinforced microalloyed titanium-based composite material according to claim 1, characterized in that, It consists of the following components by mass fraction: Ta 0.70%, Mo 0.90%, Sn 1.10%, graphene 0.90%, with the remainder being Ti and other unavoidable impurity elements.

5. The graphene-reinforced microalloyed titanium-based composite material according to claim 1, characterized in that, It consists of the following components by mass fraction: Ta 0.90%, Mo 1.10%, Sn 1.30%, graphene 1.10%, with the remainder being Ti and other unavoidable impurity elements.

6. The graphene-reinforced microalloyed titanium-based composite material according to claim 1, characterized in that: In step S1, the grinding jar needs to be cleaned with a brush and dried with water before loading the grinding balls and components. Then it needs to be cleaned and dried with anhydrous ethanol. The mass ratio of grinding balls to materials is 2:

1. Before placing the grinding jar on the ball mill, it needs to be vacuumed three times in a vacuum environment.

Citation Information

Patent Citations

  • Graphene reinforced titanium-based composite material characterized by three-dimensional network-shaped distribution, preparation method thereof and application thereof

    CN109022907A